Pengaruh Harga Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Go-Jek Di Kota Manado - Dumgair, Putra (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
The development of the online transportation industry has made competition in the market even tighter so that consumers are increasingly selective in choosing the services to be used. Given this, customer satisfaction is of course a very important factor for the existence, continuity and development of the company, in this case PT Go-Jek Indonesia. In this research, we will discuss the influence of two factors, namely price and service quality and their impact on Go-Jek customer satisfaction in Manado city. From the results of a survey conducted on 50 respondents who had used Go- Jek services several times, it was found that the two independent variables, namely price and service quality, had a significant influence both partially and simultaneously on the dependent variable, namely customer satisfaction. The results of this research can certainly be useful input and material for consideration for related parties, especially PT Go-Jek Indonesia in the Manado city area in an effort to continue to maintain and increase customer satisfaction.